Effect of graphene nanoplatelets on flame retardancy and corrosion resistance of epoxy nanocomposite coating - Siti Maznah, Kabeb; Azman, Hassan; Zurina, Mohamad; Zalilah, Sharer; Munirah, Mokhtar; Faiz, Ahmad (UTM Press, 2019)
Various concentrations of graphene nanoplatelets (GNP) i.e. 0.2, 0.4, 0.6, 0.8 and 1.0 wt. % were incorporated into the epoxy resin by sonication technique and mechanical agitation process. Limiting oxygen index (LOI) test and thermogravimetric analysis (TGA) indicated that the presence of GNP greatly enhanced the flame retardancy properties of the epoxy coating. Salt spray results obtained suggested that the addition of GNP enhanced corrosion performance and reducing the water absorption in comparison with pristine epoxy coating. Adhesion (cross-cut test) revealed that the presence of GNP showed great adhesion to substrates. Incorporation of 0.8 wt. % GNP exhibited the superior anticorrosion performance, great adhesion to subtract, and the lowest water uptake among other samples.